CONVERSATIONAL STYLE OF MALE AND FEMALE TEACHERS IN SENIOR HIGH SCHOOL - Ema Zakia; Amrin Saragih; Busmin Gurning (LINGUISTIK TERAPAN, 2019)
This research dealt with conversational style of male and female teachers in senior high school. The objectives of this study were: to investigate features of conversational style used by male and female teachers in senior high school; and to elaborate the conversational style. It was conducted using qualitative research design. The data were obtained from 4 male and 4 female teachers. 20 conversations were recorded. The instruments of collecting data were observation, recording, and interviewing adopted by Miles, Huberman, and Saldana (2014). The data were classified to the criteria of conversational style determined by Swann (2000).The findings showed there were five features of conversational style used by male and female teachers. All features of conversational style were found in realization of male and female teachers.Keywords: Conversational style, Gender and Language, Teachers‟ language.